"Our sense of wonder grows exponentially; the greater the knowledge, the deeper the mystery."

-- E.O. Wilson

Web scienceontap.blogspot.com

Thursday, July 23, 2009


Just a simple fun math diversion today that I've adapted from another blog:

-- Proof --


a + b = c.

This can then be equivalently written as:

(4a – 3a) + (4b – 3b) = 4c – 3c

After reorganizing (adding/subtracting from both sides):

4a + 4b4c = 3a + 3b3c

Take the constants out of the brackets:

4(a + bc) = 3(a + bc)

Remove the same term left and right:

4 = 3



Christie Lynn said...

Stop it! You're making my brain hurt!

Arj said...

Had a couple of emails from people frustrated at finding the flaw in the 'proof,' so for any hurting brains out there, the answer below:
==> since a+b=c, a+b-c must equal 0. This means in the very last step of dividing out a+b-c you are dividing by 0 -- A math NO-NO! (or alternatively you can say that 4x0 does equal 3x0).